2013
DOI: 10.1111/jpy.12125
|View full text |Cite
|
Sign up to set email alerts
|

Prevailing sea surface temperatures inhibit summer reproduction of the kelp Laminaria digitata at Helgoland (North Sea)

Abstract: The impact of abiotic factors on kelp sporophyte reproduction has rarely been investigated. Laminaria digitata (Hudson) J.V. Lamouroux is one of the few summer fertile Laminaria species worldwide and reproduction is subjected to relatively high water temperatures. We investigated the impact of prevailing summer temperatures (~18°C in August) on the induction of sporangia, meiospore release, and germination at the island of Helgoland (North Sea). At Helgoland, fertile sporophytes are found between April and Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 81 publications
3
70
1
Order By: Relevance
“…The reasons for this reduction are unknown but may be a consequence of competition between species, namely caused by the expansion of L. hyperborea. Recently it was shown that the reproductive efficiency of the infralittoral population of L. digitata was negatively affected in summer conditions, and that this upper population may become eradicated intermittently after warm summers (Bartsch et al 2013). In the Baltic, where L. digitata reaches its salinity limits, the recorded changes might be due to hydrological reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for this reduction are unknown but may be a consequence of competition between species, namely caused by the expansion of L. hyperborea. Recently it was shown that the reproductive efficiency of the infralittoral population of L. digitata was negatively affected in summer conditions, and that this upper population may become eradicated intermittently after warm summers (Bartsch et al 2013). In the Baltic, where L. digitata reaches its salinity limits, the recorded changes might be due to hydrological reasons.…”
Section: Discussionmentioning
confidence: 99%
“…comm. ) and are under pressure in the southern North Sea (Bartsch et al 2013). In Kongsfjorden (western Spitsbergen, Svalbard) this species considerably increased in biomass since 1996/98 at shallow sublittoral depths (Bartsch et al 2016).…”
Section: Mappingmentioning
confidence: 99%
“…(2) As high summer temperatures (>17°C) delay gametogenesis and recruitment, the potential recruitment period is shifted to cooler autumn to winter conditions. (3) As all vegetative gametophyte cells are omnipotent and may become fertile later when conditions become cooler again, zoospores released under unfavourable summer conditions are not necessarily lost from the population, as described by Bartsch et al (2013). This sequence of events would prevent the formation of juvenile sporophytes in stressful summer conditions (low nutrients, high temperatures and high irradiation) but nevertheless ensures recruitment later in the year.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing ocean temperature may drive losses of kelp canopy by limiting reproduction (Bartsch et al 2013) and growth (Bolton & Lüning 1982, Simonson et al 2015, Gao et al 2016 or through tissue degradation that increases fragmentation or mortality (Lüning 1984, Wernberg et al 2013, Simonson et al 2015. Proliferation of turf algae following canopy removal is intensified by factors that directly stimulate turf growth, including increases in ocean temperatures (Connell & Russell 2010).…”
Section: Photo: Robert Scheiblingmentioning
confidence: 99%